Analysis of a rotary pump with two sectional impellers - Fischer- Szava, Gabriel; Băran, Nicolae; Constantin, Mihaela; Nicolau, Ana-Maria; Adil Abdul-Nabe, Rana; Ghioca, Sevastiana Areta; Dăescu, Georgiana (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The presented study shows aspects related to the fluid flow inside a rotary machine; this type of machine can be utilized as a ventilator, air pump or blower. Relations for computing the driving power of this pump as well as the fluid flow rate of transported are presented. The sealing between the impellers and between the impellers and the machine casing is studied and the advantages of different types of impeller shapes are specified.